Peran Majelis Ulama Indonesia Kabupaten Mandailing Natal Dalam Pelaksanaan Manasik Haji - Abdi Kurniawan; Mhd. Rasid; Muhammad Yusuf; Saidatul Alawiyah; Awaluddin Awaluddin; M. Habiburrahman Al Makky (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research aims to assess the extent of the role of the Mandailing Natal Regency MUI in implementing the Hajj rituals for prospective Hajj pilgrims, kindergarten children and Islamic boarding school students. The implementation of this research involved various individuals from various parties involved in this community service effort. This research method uses the Participation Action Research (PAR) method. The results of this service research show that the role of the Indonesian Ulema Council of Mandailing Natal Regency in implementing the Hajj rituals is very important because it can assist the duties of the Ministry of Religion and help prospective Hajj pilgrims know and understand the process of carrying out the Hajj pilgrimage. Furthermore, this analysis also shows that there are several methods used by the Mandailing Natal Regency MUI in carrying out the Hajj rituals.